The role of the family network when raising a child with a disability in low- and middle-income countries - Bizzego, Andrea (2021)
Family plays a role in supporting child development, by facilitating caregiving and other parental practices. Low- and middle-income families typically have a complex structure with many relatives living together in the same household. The role of family and family complexity in the caregiving of children with disabilities is still unknown. In this study, we use data from N = 22,405 children with severe (N = 876) and mild or no disability (N = 21,529) from a large dataset collected in the 2005–2007 Multiple Indicator Cluster Survey. In particular, we adopt PageRank, a well-known algorithm used by search engines, to quantify the importance of each child in the family network. We then analyze the level of caregiving the child received in light of the child’s importance and developmental status, using a generalized linear model. Results show a main effect of child’s importance and of the interaction of child’s importance and developmental status. Post hoc analysis reveals that higher child importance is associated with a better caregiving outcome only for children with mild or no disability.